Comprehensive Analysis of Disease-Related Genes in Chronic Lymphocytic Leukemia by Multiplex PCR-Based Next Generation Sequencing - Vollbrecht, Claudia; Mairinger, Fabian Dominik; Koitzsch, Ulrike; Peifer, Martin; Koenig, Katharina; Heukamp, Lukas Carl; Crispatzu, Giuliano; Wilden, Laura; Kreuzer, Karl-Anton; Hallek, Michael; Odenthal, Margarete; Herling, Carmen Diana; et al. (PloS one, 2015)
High resolution molecular studies have demonstrated that the clonal acquisition of gene mutations is an important mechanism that may promote rapid disease progression and drug resistance in chronic lymphocytic leukemia (CLL). Therefore, the early and sensitive detection of such mutations is an important prerequisite for future predictive CLL diagnostics in the clinical setting. Here, we describe a novel, target-specific next generation sequencing (NGS) approach, which combines multiplex PCR-based target enrichment and library generation with ultra-deep high-throughput parallel sequencing using a MiSeq platform. We designed a CLL specific target panel, covering hotspots or complete coding regions of 15 genes known to be recurrently mutated and/or related to B-cell receptor signaling. High-throughput sequencing was performed using as little as 40 ng of peripheral blood B-cell DNA from 136 CLL patients and a dilution series of two ATM- or TP53-mutated cell lines, the latter of which demonstrated a limit of mutation detection below 5%. Using a stringent functional assessment algorithm, 102 mutations in 8 genes were identified in CLL patients, including hotspot regions of TP53, SF3B1, NOTCH1, ATM, XPO1, MYD88, DDX3X and the B-cell receptor signaling regulator PTPN6. The presence of mutations was significantly associated with an advanced disease status und molecular markers of an inferior prognosis, such as an unmutated IGHV mutation status or positivity for ZAP70 by flow cytometry. In summary, targeted sequencing using an amplicon based library technology allows a resource-efficient and sensitive mutation analysis for diagnostic or exploratory purposes and facilitates molecular subtyping of patient sets with adverse prognosis.